2018
DOI: 10.3389/fnana.2018.00079
|View full text |Cite
|
Sign up to set email alerts
|

The Mormyrid Optic Tectum Is a Topographic Interface for Active Electrolocation and Visual Sensing

Abstract: The African weakly electric fish Gnathonemus petersii is capable of cross-modal object recognition using its electric sense or vision. Thus, object features stored in the brain are accessible by multiple senses, either through connections between unisensory brain regions or because of multimodal representations in multisensory areas. Primary electrosensory information is processed in the medullary electrosensory lateral line lobe, which projects topographically to the lateral nucleus of the torus semicirculari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 108 publications
(166 reference statements)
0
5
0
Order By: Relevance
“…Golgi studies reported axonal projections from TL granule cells to the most superficial layer of the tectum, the marginal layer or stratum marginale (Sala, 1895;Sajovic and Levinthal, 1982). This TL efferent connection was then traced experimentally to the optic tectum in the holostean longnose gar (Lepisosteus osseus; Northcutt and Butler, 1980) and several teleosts (Grover and Sharma, 1981;Luiten, 1981;Northcutt, 1982;Wullimann and Northcutt, 1990;Ito et al, 2003;Xue et al, 2003;Folgueira et al, 2007;Zeymer et al, 2018). Granule cell axons run in the marginal layer parallel to the surface of the tectum, in a manner that is similar to cerebellar parallel fibers, and synapse onto the spiny, branched dendrites of pyramidal or type I cells Vanegas et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Golgi studies reported axonal projections from TL granule cells to the most superficial layer of the tectum, the marginal layer or stratum marginale (Sala, 1895;Sajovic and Levinthal, 1982). This TL efferent connection was then traced experimentally to the optic tectum in the holostean longnose gar (Lepisosteus osseus; Northcutt and Butler, 1980) and several teleosts (Grover and Sharma, 1981;Luiten, 1981;Northcutt, 1982;Wullimann and Northcutt, 1990;Ito et al, 2003;Xue et al, 2003;Folgueira et al, 2007;Zeymer et al, 2018). Granule cell axons run in the marginal layer parallel to the surface of the tectum, in a manner that is similar to cerebellar parallel fibers, and synapse onto the spiny, branched dendrites of pyramidal or type I cells Vanegas et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we have demonstrated that the V motor system receives visual information from the optic tectum and via the two pretectal nuclei, as mentioned above. Recent experiments done by Zeymer et al () have revealed new anatomical evidence for an ascending afferent projection from the trigeminal sensory column to the optic tectum and to the lateral nucleus of the torus semicircularis. This suggests that the optic tectum is also an interface for the integration of visual, electrosensory and somatosensory information, providing afferent input to the V motor nucleus.…”
Section: Discussionmentioning
confidence: 97%
“…However, some considerable variation is present in the labeling used in studies by different authors. The most recent study has been published by Zeymer, von der Emde, and Wullimann () using an updated nomenclature established by Wullimann, where possible concordances are identified.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the zebrafish OT appears involved as a higher center of the lateral line circuitry, but hardly of the auditory one. Torotectal projections were reported in goldfish (Grober and Sharma, 1981), and in mormyrids, the OT is also topographically related to the mediodorsal and lateral regions of the TS (Haugedé‐Carré, 1983; Zeymer et al., 2018). The midbrain tegmentum does not show toral (TSc) afferent neurons in zebrafish, unlike that reported in carp (Echteler, 1984, 1985).…”
Section: Discussionmentioning
confidence: 98%